Comparison of peptide nucleic acid fluorescence in situ hybridization assays with culture‐based matrix‐assisted laser desorption/ionization‐time of flight mass spectrometry for the identification of bacteria and yeasts from blood cultures and cerebrospinal fluid cultures. (13th January 2014) - Calderaro, A.; Martinelli, M.; Motta, F.; Larini, S.; Arcangeletti, M. C.; Medici, M. C.; Chezzi, C.; De Conto, F.; Allerberger, F.
Abstract Peptide nucleic acid fluorescence in situ hybridization (PNA FISH) is a molecular diagnostic tool for the rapid detection of pathogens directly from liquid media. The aim of this study was to prospectively evaluate PNA FISH assays in comparison with culture‐based matrix‐assisted laser desorption/ionization‐time of flight mass spectrometry (MALDI‐TOF MS) identification, as a reference method, for both blood and cerebrospinal fluid (CSF) cultures, during a 1‐year investigation. On the basis of the Gram stain microscopy results, four different PNA FISH commercially available assays were used ('Staphylococcus aureus/CNS', 'Enterococcus faecalis/OE', 'GNR Traffic Light' and 'Yeasts Traffic Light' PNA FISH assays, AdvanDx). The four PNA FISH assays were applied to 956 positive blood cultures (921 for bacteria and 35 for yeasts) and 11 CSF cultures. Among the 921 blood samples positive for bacteria, PNA FISH gave concordant results with MALDI‐TOF MS in 908/921 (98.64%) samples, showing an agreement of 99.4% in the case of monomicrobial infections. As regards yeasts, the PNA FISH assay showed a 100% agreement with the result obtained by MALDI‐TOF MS. When PNA FISH assays were tested on the 11 CSF cultures, the results agreed with the reference method in all cases (100%). PNA FISH assays provided species identification at least one work‐day before the MALDI‐TOF MS culture‐based identification. PNA FISH assays showed an excellent efficacy in the prompt identification of main pathogens, yielding a significant reduction in reporting time and leading to more appropriate patient management and therapy in cases of sepsis and severe infections.